Pathogen identification and biological fungicides screening for Plumbago auriculata blight in China - Liu, Ming; Guo, Tiantian; Yan, Hao; Yuan, Yue; Xiao, Zhien; Liu, Yuxin; Zhang, Shaotian; Lyu, Fengqing; Jing, Shan; Yin, Fuqiang (Frontiers in Microbiology, 2025)
Plumbago auriculata is an important ornamental horticultural plant with high ornamental value. Plumbago auriculata blight was first detected in 2023 in Wanzhou District, Chongqing City, China. This disease seriously reduces the ornamental value of P. auriculata. The disease was characterized by the yellowing and drying up of the apex in the early stage and the drying up and death of the entire aboveground part in the later stage. To identify the pathogenic fungus of P. auriculata blight in Wanzhou district of Chongqing and to screen effective biological pesticides for controlling the disease, the pathogen was isolated and cultured using the tissue separation method. The pathogens were identified by morphology combined with multigene analysis. Cross-pathogenicity experiments were conducted on two other horticultural plants using the pathogen. Biological fungicides were screened by an indoor toxicity test. Combined with the potted plant prevention effect experiment, the control efficacy of the biological fungicide was evaluated. The results showed that isolates L9 and L11 colonies have white cotton flocculent aerial mycelium. The macroconidia are falcate, prominently cell papillate, and hooked. Numerous chlamydia spores were observed through PDA. L9 and L11 were identified by phylogenetic analysis (internal transcribed spacers, RNA polymerase II second largest subunit, translation elongation factor 1 alpha, and calmodulin) and clustered together with Fusarium ipomoeae in the same single clade. This is the first report that F. ipomoeae causes blight on P. auriculata in China. Fusarium ipomoeae was pathogenic to Prunus serrulata and Heptapleurum arboricola. The results of the indoor toxicity test showed that the inhibitory effect of 0.4% osthole SL on F. ipomoeae was significant, with an EC50 value of 1.089 μg/mL. 0.4% osthole SL has a good prevention and control effect on P. auriculata blight, with a control efficacy of 88%. Osthole can be used for the prevention and control of P. auriculata blight. The results provided the foundation for the recognition and green control of P. auriculata blight caused by F. ipomoeae.